ОСОБЕННОСТИ ХОЗЯЙСТВА КАРАКАЛПАКОВ ФЕРГАНСКОЙ ДОЛИНЫ В ИСТОРИЧЕСКОМ КОНТЕКСТЕ - Давлетияров М.М, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The paper considers the question of the traditional form of the Karakalpak economy, which has been preserved to this day. This type of complex economy is peculiar to the ancestors of the Karakalpaks from ancient times, who lived on the territory of the Aral Sea region.